A new genus and species of Leptoconopinae (Diptera: Ceratopogonidae) from Lower Cretaceous Baskinta amber outcrop in Lebanon - Pielowska-Ceranowska, Agata; Azar, Dany; Szwedo, Jacek (European Journal of Taxonomy, 2023)
A new fossil ceratopogonid genus and species from Lower Cretaceous Lebanese amber, Baskintoconops maaloufi Pielowska-Ceranowska gen. et sp. nov., is described and illustrated. The studied material originates from a newly discovered amber site in the Lebanese village Baskinta at a locality dubbed Qanat Bakish. The described genus is typified by its wing venation pattern combining characters of genera Fossileptoconops and Jordanoconops belonging to the subfamily Leptoconopinae.